Spontaneous abortions and congenital malformations among women exposed to tetrachloroethylene in dry cleaning. Issue 4 (December 1989) - Kyyrönen, P; Taskinen, H; Lindbohm, M L; Hemminki, K; Heinonen, O P
Abstract : STUDY OBJECTIVE: The aim of the study was to determine whether exposure to tetrachloroethylene during the first trimester of pregnancy has harmful effects on pregnancy outcome. DESIGN: The study used record linkage identification of cases and case-control comparison. SETTING: The study involved dry cleaner and laundry workers throughout Finland who had become pregnant during the study period. Controls were age matched but otherwise unselected women giving birth to normal babies in the study period. SUBJECTS: Cases were defined as women who had been treated for spontaneous abortion or had delivered a malformed child. Out of 5700 workers nearly half had been pregnant during the study period. One pregnancy only was randomly selected for study per worker, and the final study population was 247 women with spontaneous abortions and 33 with malformed infants. Three age matched controls were selected for each abortion case and five for each malformation case. MEASUREMENTS AND MAIN RESULTS: Three women out of four had worked in early pregnancy. Exposure information was collected from 1108 women by mailed questionnaires, with a 77% response, and was partly confirmed by biological monitoring data. Exposure to tetrachloroethylene was found to be significantly associated with spontaneous abortions (odds ratio 3.6, p less than 0.05). CONCLUSION: The findings, together with other available data, indicate that exposure of pregnant women to tetrachloroethylene needs to be minimised.